Mathematical model of the pulse generation of decontaminating aerosols - Kudryashova, Olga B.; Sokolov, Sergei D.; Zhukov, Ilya A.; Vorozhtsov, Alexander B. (Materials)
A mathematical model of the pulse generation of decontaminating aerosols utilizing the energy of high-energy materials (HEM) is proposed with account for the physical and chemical properties of the atomized substance, HEM characteristics, and gas generator parameters. Such a model is needed to counter the environmental hazards, process emissions, and terrorist attacks with hazardous and dangerous aerosols. Another aspect of the problem is the danger of biological aerosols carrying viral or microbial particles that are spread naturally or induced using biological weapons. In many cases, the mission is not only to neutralize aerosol particles in indoor air and on surfaces but also to do it quickly. In this regard, an attractive option is the pulse method for generating special aerosols aimed at quickly, within a few seconds, creating a cloud of particles that will interact with hazardous aerosol particles and decontaminate them. HEM energy is proposed to be used for the pulse generation of such aerosols. It is important not only to atomize the decontaminating aerosol quickly and evenly in space but also to preserve the useful physical and chemical properties of the particles. To test the regimes and methods of pulse generation, an adequate mathematical model of the process is required, which is proposed in this manuscript.